A preliminary study on the effect of pharmacist counseling on awareness of and willingness to quit smoking in Malaysian population - Babar, Zaheer-ud-din; Irfan Bukhari, Nadeem; Sarwar, Wasim; Efendie, Benny; Pereira, Rosa; Nik Mohamed, Mohamad Haniki (SpringerLink, 2007)
Objectives: This paper presents an outcome of pharmacist counseling among Malaysian smokers for their awareness of and willingness to quit smoking. Method: It was a cross-sectional study during a 3-day public health campaign at a shopping complex. Each self-referred participant was asked to complete a questionnaire apart from the question regarding improvement, and if any in their awareness and willingness to quit smoking, were asked to respond after counseling. Pharmacists counseled each participant about smoking cessation strategies and smoking related diseases. The data were analyzed by v2 test. Results: Among respondents, 25.5% had been smoking for more than 10 years, 31% for 5–10 years, 25.4% for 2–5 years and 18.3% for 1–2 years. The participants declaring no awareness about smoking were 22.9%, with little awareness 44.3%, having moderate awareness 25.7% and with considerable awareness were 7.1%. After counseling, 4.1% revealed unawareness, 17.8% little awareness, 43.8% moderate and 34.2% had considerable awareness on the above aspects. The post counseling awareness on smoking was observed to be significantly higher (P<0.01). Among smokers studied, 67% showed willingness to quit smoking. Conclusion: Increase in awareness of and willingness to quit smoking reflects